1984
DOI: 10.1080/10862968409547523
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Three Forms of Summarization Instruction on Sixth Graders' Summary Writing and Comprehension

Abstract: Three forms of summarization instruction comprised the treatment and control conditions explored in this study of sixth graders. The two treatment groups received direct instruction in either a rule-governed approach to summarization or an intuitive approach. A control group simply received advice to find main ideas with no explicit modeling. Two dependent measures were used to judge the efficacy of the three instructional approaches to summarization: (a) a paragraph summary writing task and (b) a standardized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(46 citation statements)
references
References 4 publications
1
40
0
5
Order By: Relevance
“…McNail ve Donant'ın (1982) kural odaklı yaklaşımına göre özet yazmada altı kural bulunmaktadır. Bunlar aşama aşama şöyledir: Gereksiz bilgi veya maddeleri silin, önemli ancak gereğinden fazla bilgiyi silin, birkaç farklı madde için bir üst başlık oluşturun, bir eylemin bileşenleri için bir üst başlık oluşturun, konu cümlesi seçin, konu cümlesi yoksa kendiniz bir konu cümlesi oluşturun (aktaran Been ve Steenwyk, 1984). Marzano (2010) özet yazmada etkili olan beş temel strateji olduğunu vurgulamıştır.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
See 1 more Smart Citation
“…McNail ve Donant'ın (1982) kural odaklı yaklaşımına göre özet yazmada altı kural bulunmaktadır. Bunlar aşama aşama şöyledir: Gereksiz bilgi veya maddeleri silin, önemli ancak gereğinden fazla bilgiyi silin, birkaç farklı madde için bir üst başlık oluşturun, bir eylemin bileşenleri için bir üst başlık oluşturun, konu cümlesi seçin, konu cümlesi yoksa kendiniz bir konu cümlesi oluşturun (aktaran Been ve Steenwyk, 1984). Marzano (2010) özet yazmada etkili olan beş temel strateji olduğunu vurgulamıştır.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Zaman eklerinin kullanımıyla ilgili olarak alanyazın tarandığında özellikle yabancı kaynaklarda geniş zaman ekinin (-Ar/Ir) kullanımı tavsiye edilmektedir Güneş, 2013;Lake, 2005; "How to Write a Summary," t.y.). Birçok kaynakta ise özette kullanılması gereken zaman konusunda herhangi bir bilgiye rastlanmamıştır (Gupta ve Lehal, 2010;Been ve Steenwyk, 1984;Kitchakarn, 2012;Williams, 2012;Deneme, 2009;Baleghizadeh ve Babapour, 2011). Bu bilgilerden hareketle 2. hafta MÖYS bilgisi aktarılırken öğrencilerin Türkçenin geniş zaman eklerinden faydalanabilecekleri bilgisi verilmiştir.…”
Section: Resim 2 Paragraf Sayısına İlişkin öRnek Resimunclassified
“…For example, Brown & Day (1983) found that children have difficulty summarizing what they have read unless they are taught how to summarize stories. When students are taught how to summarize stories, their ability to answer questions about passages they read improves (Bean & Steenwyk, 1984;Rinehart, Stahl & Erickson, 1986;Taylor & Beach, 1984). In one study, Cook & Mayer (1988) taught students how to outline paragraphs found in their science textbooks.…”
Section: Strategy Training In Reading Comprehensionmentioning
confidence: 99%
“…Regarding that, the studies developed by Cook & Mayer (1983), Mayer & Bromage (1980), and Derry & Murphy (1986) stand out. It has been proved that high-skilled students at writing summaries used to select and organize the information before writing the summary (Bean & Steenwyk, 1984). Researchers also have found that less-skilled students at writing summaries can be benefited from the direct teaching on strategies for selecting and organizing information (Bean & Steenwyk, 1984;Mayer R. , 2002;Ponce, Mayer, & Mario, 2013).…”
Section: Teaching Phasementioning
confidence: 99%